FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN STATUS GIZI IBU HAMIL DI PUSKESMAS SIDOREJO KOTA LUBUKLINGGAU - Zuraidah, Zuraidah (Politeknik Kesehatan Kemenkes Bengkulu, 2016)
The nutritional status of pregnant women is one of the indicators to measure thenutritional status of the community. If the input of nutrition for pregnant women of thefood is not balanced with the needs of the body, there will be a deficiency of nutrients.Maternal Mortality become one important indicator in determining the degree of publichealth. According to the World Health Organization (WHO) in 2005 in developed countriesthe maternal mortality rate ranged from 5-10 per 100,000 live births, while in countriesemerging range between 750-1000 per 100,000 live births (Winkjosastro, 2005). Thepurpose of this study to determine the factors-factors related to the nutritional status ofpregnant women. The independent variables of this study are education, income andknowledge while the dependent variable is the nutritional status of pregnant women. Thisresearch uses a survey method with cross sectional analytic. The population in this studywere all pregnant women at health centers Sidorejo Lubuklinggau is numbered 40 pregnantwomen. The sample used is total sam-pling. Collecting data by distributing questionnairesto the respondents. The survey results revealed that respondents with low education,there are 23 (57.5%), lower income as many as 30 (75%), and respondents who haveenough knowledge-less 27 (67.5%), and respondents malnutrition status as 22 (55%). Aftertesting the chi square statistic diketahahui these three variables have a significant associationwith the nutritional status of pregnant women. Expected for health centers to providehealth education on nutrition in pregnant women, and also provide nutritious supplementaryfeeding program for pregnant women